A semiotic analysis of ‘individualism’ and ‘collectivism’: the Global Bersih 3.0 website - Mokhtar, Aida (2012)
A semiotic analysis was carried out on the Global Bersih 3.0 Website. Hofstede's cultural values of individualism and collectivism were at the centre of the analysis.